RATANA FIELD, POTWAR FOLD BELT, NORTHERN PAKISTAN: HIGH INTENSITY FRACTURE ZONES RELATED TO MAJOR THRUST FAULTS AS REVEALED BY SEISMIC FRACTURE PREDICTION. (23rd June 2022) - Shoaib, Khalid; Zafar, Zaheer A.; Raja, Zeeshan Ali; Burley, Stuart D.
Abstract : The Northern Potwar Deformed Zone (NPDZ) of the frontal Himalayas in northern Pakistan hosts many oil and gas fields located in thrust sheets and associated folds. The presence of fractures in Paleogene carbonates at >3 km target depths with very little or no primary porosity is an essential part of reservoir storage and connectivity. Predicting fracture presence, distribution and orientation is therefore key to successful exploration, appraisal and field development in the NPDZ. The Ratana field is an under‐developed fractured carbonate reservoir in the NPDZ. Advanced offset vector tile (OVT) PSTM and PSDM processing of a new generation of wide azimuth 3D seismic acquired across the field followed by seismic attribute generation and fracture modelling was used to investigate structural complexities and image fracture networks. Fracture strike characteristics are revealed by PSDM seismic attributes, OVT fracture prediction, FMS/FMI data and structural interpretation across a range of scales. The resulting seismic images show the presence of major WNW‐ESE trending back thrusts which cross the field, and predict that steeply‐dipping fracture systems are spatially associated with these thrusts. The strike of the OVT‐predicted fractures is consistent with the regional trend of the Ratana field bounding thrusts, as well as with the orientation of fractures indicated from FMI/FMS logs. Fractured reservoir is best developed in the Paleocene Patala and Lockhart Formation limestones but is poor in the Eocene Sakesar Formation. Fractured limestone reservoirs occur in the western part of the field where thrust intensity is high, but are less well developed in the gently folded anticline in the eastern part of the field. OVT fracture prediction surface maps are consistent with production data from the field in that areas of high fracture intensity in wells Ratana‐2 and Ratana‐4 are associated with higher production compared to the less well fractured areas around the Ratana‐1 and Ratana‐3 wells. The advanced seismic acquisition and processing is thus an exceptional example of a step change in seismic imaging at the reservoir and deeper levels, enabling compartment and fracture prediction to provide the Ratana field with a new lease of life. This fracture prediction approach provides a new structural framework for further exploration across the NPDZ and also potentially in other onshore fold‐and‐thrust belts.